2006
DOI: 10.1093/toxsci/kfl098
|View full text |Cite
|
Sign up to set email alerts
|

Hormesis Outperforms Threshold Model in National Cancer Institute Antitumor Drug Screening Database

Abstract: Which dose-response model best explains low-dose responses is a critical issue in toxicology, pharmacology, and risk assessment. The present paper utilized the U.S. National Cancer Institute yeast screening database that contains 56,914 dose-response studies representing the replicated effects of 2189 chemically diverse possible antitumor drugs on cell proliferation in 13 different yeast strains. Multiple evaluation methods indicated that the observed data are inconsistent with the threshold model while suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
124
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 135 publications
(133 citation statements)
references
References 9 publications
9
124
0
Order By: Relevance
“…Cd, As, Hg) (Calabrese and Blain, 2004;Helmcke et al, 2010), dioxins (Rozman et al, 2005), pesticides (Cedergreen, 2008) and therapeutic agents (Calabrese and Baldwin, 2003a). The repeated occurrence of low-dose stimulation has led to suggestions that the hormesis model could even replace the logistic as the default in toxicology (Calabrese, 2008;Calabrese et al, 2006). This could have profound implications for chemical management, as regulation using hormesis (over traditional logistic models) could both alter permissible levels (Calabrese and Cook, 2005) and also providing a public perception of risk that "a little stress might be good for you" or more eloquently "what doesn't kill you makes you stronger"…”
Section: Life-cycle Toxicity Tests For Dcmu and Ag Npsmentioning
confidence: 99%
“…Cd, As, Hg) (Calabrese and Blain, 2004;Helmcke et al, 2010), dioxins (Rozman et al, 2005), pesticides (Cedergreen, 2008) and therapeutic agents (Calabrese and Baldwin, 2003a). The repeated occurrence of low-dose stimulation has led to suggestions that the hormesis model could even replace the logistic as the default in toxicology (Calabrese, 2008;Calabrese et al, 2006). This could have profound implications for chemical management, as regulation using hormesis (over traditional logistic models) could both alter permissible levels (Calabrese and Cook, 2005) and also providing a public perception of risk that "a little stress might be good for you" or more eloquently "what doesn't kill you makes you stronger"…”
Section: Life-cycle Toxicity Tests For Dcmu and Ag Npsmentioning
confidence: 99%
“…A detailed description of the NCI database, experimental design, and methods is given in Calabrese et al (2006). Briefly, data from stage 2 of the NCI testing procedure were evaluated on 2189 compounds considered to be E. J.…”
Section: A High Through-put Study Of 2189 Chemicals On 13 Strains Of mentioning
confidence: 99%
“…A value of 5% was selected for the BMD, in part because this percentage was approximately one standard deviation of control response. The BMD 5 was estimated by a linear interpolation between the concentration immediately above and below the 95% response, similar to Figure 1 in Calabrese et al (2006). Doses used to derive the BMD 5 were not included in the low-dose range.…”
Section: Determining a Benchmark Dosementioning
confidence: 99%
“…These compounds were tested on a panel of 13 yeast strains, each having one or two mutations affecting damage-response functions (DNA damage repair or cell cycle control) homol-ogous to those mutated in human cancers. Previous analyses of these NCI data have shown that responses below the toxic threshold were poorly predicted by the threshold model, yet highly consistent with a hormetic, inverted U-shaped concentration-response model (Calabrese et al 2006a(Calabrese et al , 2008. The initial studies evaluated the individual responses of concentrations and their replication below estimated Benchmark Doses (BMDs) but they did not explore the individual concentration-response relationships or the magnitude of stimulation with respect to hormesis.…”
Section: Introductionmentioning
confidence: 99%